ANALYSIS OF THE RELIABILITY AND VALIDITY OF ACADEMIC PROCRASTINATION QUESTIONNAIRES USING RASCH MODEL - Monica Boreel; Mamat Supriatna (OPTIMA: Journal Of Guidance and Counseling, 2022)
The analysis aims to validate and develop instruments regarding academic procrastination of Indonesian Korean Pop (K-Pop) fans. In 2021, research was carried out with a survey method on 5 boys and 171 teenage girls who are K-Pop fans spread across Indonesia. The research method used is a quantitative research method which contains 50 statement items with 5 answer choices using a Likert scale model. Data analysis using the Rasch model with the help of the Winstep application. The survey results show the value Cronbach Alpha which describes the interaction between the person and the items as a whole is 0.90 and is included in the high category. The value of person reliability and the value of item reliability are both in the special category with values of 0.89 and 0.99. This shows an indicator of the consistency of participants' answers with an indicator of very good item quality.